Bone metastases in newly diagnosed patients with thyroid cancer: A large population-based cohort study - Zhang, Ruiguo; Zhang, Wenxin; Wu, Cailan; Jia, Qiang; Chai, Jinyan; Meng, Zhaowei; Zheng, Wei; Tan, Jian (Frontiers in Oncology, 2022)
Background: Population-based estimates of the incidence and prognosis of bone metastases (BM) stratified by histologic subtype at diagnosis of thyroid cancer are limited. Methods: Using multivariable logistic and Cox regression analyses, we identified risk factors of BM and investigated prognostic survival of BM patients between 2010 and 2015 via the Surveillance, Epidemiology, and End Result (SEER) database. Results: Among 64083 eligible patients, totally 347 patients with BM at the time of diagnosis were identified, representing 0.5% of the entire cohort but 32.4% of the subset with metastases. BM incidence was highest (11.6%) in anaplastic thyroid cancer (ATC), which, nevertheless, was highest (61.5%) in follicular thyroid cancer (FTC) among subset with metastases. Median overall survival among BM patients was 40.0 months, and 1-, 3- and 5-year survival rates were 65.2%, 51.3% and 38.7%, respectively. Compared with papillary thyroid cancer (PTC), FTC (aOR, 6.33; 95% CI, 4.72-8.48), medullary thyroid cancer (MTC) (aOR, 6.04, 95% CI, 4.09-8.92) and ATC (aOR, 6.21; 95% CI, 4.20-9.18) significantly increased the risk of developing BM. However, only ATC (aHR, 6.07; 95% CI, 3.83-9.60) were independently associated with worse survival in multivariable analysis. Additionally, patients with BM alone (56.5%) displayed the longest median survival (66.0 months), compared with those complicated with one extraskeletal metastatic site (lung, brain or liver) (35.2%; 14.0 months) and 2 or 3 sites (8.3%; 6.0 months). The former 5-year overall survival rate was 52.6%, which, however, drastically declined to 23.0% in patients with one extraskeletal metastatic site and 9.1% with 2 or 3 sites. Conclusion: Closer bone surveillance should be required for patients with FTC, MTC and ATC, and extraskeletal metastases at initial diagnosis frequently predict poorer prognosis.